Absence of electrocardiographic left ventricular hypertrophy is associated with increased mortality after transcatheter aortic valve replacement. Issue 9 (21st August 2018) - Kampaktsis, Polydoros N.; Ullal, Ajayram V.; Swaminathan, Rajesh V.; Minutello, Robert M.; Kim, Luke; Bergman, Geoffrey S.; Feldman, Dmitriy N.; Singh, Harsimran; Wong, Shing Chiu; Okin, Peter M.
Abstract : Background: Electrocardiographic (ECG) left ventricular hypertrophy (LVH) has been associated with increased mortality in patients with asymptomatic aortic stenosis (AS) and hypertension. However, patients with symptomatic AS undergoing transcatheter aortic valve replacement (TAVR) have higher percentages of myocardial fibrosis or amyloidosis that have been associated with decreased ECG voltage and worse outcomes. Hypothesis: We tested the hypothesis that baseline ECG LVH is independently associated with increased all‐cause mortality after TAVR. Methods: A total of 231 patients (96 men; mean age 84.7 ± 7.8 years) that underwent TAVR at our institution were included. Cornell voltage, defined as SV3 + RaVL, was used to assess for presence of ECG LVH using gender‐specific cut‐off values. We used the Kaplan‐Meier estimator to derive survival curves. Multivariate Cox regression analysis was used to compare mortality between patients without vs with ECG LVH and adjust for echocardiographic LVH and predictors of mortality in this cohort. Results: Over a follow‐up time of 16.3 ± 10.4 months, the absence of ECG LVH was significantly associated with increased mortality (40.4% vs 23.6% at 2‐years, log rank P = 0.003). After adjusting for echocardiographic LVH and predictors of mortality in our cohort, the absence of ECG LVH remained a predictor of increased mortality (HR = 1.79, CI 95% 1.02‐3.14, P = 0.042). Conclusions: The absence of ECG LVH was independently associated with increased mortality in patients undergoing TAVR. Baseline ECG may have an important prognostic role in these patients and could lead to further testing to evaluate for myocardial fibrosis or amyloidosis.